Spirituality and Emotional Intelligence in university students of the city of Ayacucho - Josselyn Miguel-Rojas; Edwin Jesús Vílchez-Quevedo; Mario Reyes-Bossio (Interacciones)
This research aims to find the existing correlation between Emotional Intelligence (EI) and Spirituality in university students of the city of Ayacucho. We opted for a quantitative method, of correlational type transactional design. To this end, we had a sample of 195 university students from two private Ayacucho universities, of which 41% are male and 59% are female, with an age range between 18 and 38 years (M = 20.43). The Trait Meta-Mood Scale-24 Questionnaire and the Spirituality Questionnaire; both adapted to the Peruvian population. We analyzed the correlations of the dimensions of both; obtaining positive correlations between all dimensions of IE with the dimensions of Spirituality; so it is concluded that both constructs are correlated. Likewise, the analyzes carried out show that there are significant differences in the explicit assessment of spirituality according to sex; specifically women score more in this regard. It can also be highlighted that the self-awareness dimension of the Spirituality questionnaire presents the strongest correlations with the Emotional Intelligence dimensions.